Perceptions of students on factors that constrain their involvement in quality assurance and promotion in two comprehensive universities in South Africa - Moyo, C.S.; Boti, Z. (South African Journal of Higher Education, 2020)
The need for student involvement in quality assurance and promotion in higher education has been a topical issue for a couple of decades. This is because students are valuable stakeholders who are at the receiving end of the higher education delivery chain and their contribution to quality assurance processes and promotion cannot be underscored. Various researchers have alluded to the fact that when students participate in quality assurance and promotion processes as joint partners, their desire to see the processes succeed would be re-invigorated. While it is easy to understand and appreciate the value of involving students in quality assurance and promotion processes, the literature reviewed has shown that, in practice, not much is happening in this regard. The article explored the perceptions of students from two comprehensive universities in South Africa on the factors that constrain their involvement in quality assurance and promotion processes in their respective higher education institutions and their possible solutions. Convenience sampling was used to select student respondents at the two selected comprehensive universities. Semi-structured questionnaires were sent to student participants to complete and the responses were coded and analysed using the Thematic Analysis Approach. The results of the study showed that the lack of knowledge on quality and quality assurance issues, lack of engagement platforms and lack of involvement in institutional decision-making processes were some of the challenges constraining the participation of students in processes pertaining to quality assurance. Some of the solutions to mitigate against the challenges proffered by students included having tutorials on quality and quality assurance issues, recognition of students as co-partners in the implementation of all academic processes and creating platforms to enable students, academic staff and management to engage one another on quality and quality assurance related issues.